STUDI KATEGORISASI KONSERVASI PADA KOMPLEK SUSTERAN BANGKONG SEMARANG DARI PENDEKATAN DISIPLIN ARSITEKTUR - Wahyuningrum, Sri Hartuti; Suprijadi, Bambang; Tudjono, Sri (architecture department, Engineering faculty, Universitas Diponegoro, 2016)
Designing architecture development for Heritage Building should handled in carefully attention due to regulation has been protected the artefact. Most of development actions such as rehabilitation, renovation,redesign or development the individual building or building complex are related to develop the building into new function or other development in the context of extention of the needs. Conservation Catagorysation Study is one of the procedure can be used in which is provided through observation stage,documentation, catagorysation analysis to the heritage building complex as approach strategy before provide designing architecture developmentThis research just an example of guidline technique in the process of architectural design in developing heritage building complex based on preservationconservation strategies.Specific approach of architectural context will provide in the future continuing research from other discipline of approach such as archeologies approach to bring final conservation catagorysation comprehensively.